MAKNA QIRAAT AL-QUR'AN DAN KAIDAH SISTEM QIRAAT YANG BENAR - Syamsul Muarif; Arina Hidayati; Halimah (CV. Adiba Aisha Amira, 2022)
Qira'at in this discussion is the way of pronouncing the recitations of the Qur'an as spoken by the Prophet or as spoken by the companions in front of the Prophet and then he recites them and is considered correct if there is a match with Arabic, there is a match with the manuscripts and the sanad is valid. the qira'at.